As innovations drive economic growth, do they also raise well-being? - Martin Binder; Ulrich Witt (Max Planck Institute of Economics, 2011)
While there is little doubt that innovations drive economic growth, their effects on well-being are less clear. One reason for this are ambivalent effects of innovations on well-being that result from pecuniary and technological externalities of innovations, argued to be inevitable. Another major reason lies in the fact that, as a result of innovations, preferences can change over time. Under such conditions, a time-consistent measuring rod for changes in well-being is hard to construct. Existing conceptions of well-being are shown not yet to solve the problem in a way that provides an unambiguous answer to the question in the title.
urn:nbn:de:gbv:27-20110630-114932-7
Keywords: D63; I31; O00; 330; innovations; growth; welfare; well-being; preference change; Innovation; Wirtschaftswachstum; Lebensqualität; Externer Effekt; Präferenztheorie; Theorie